Women in society. South Africa - Rissik, Dee, 1953- (New York : M. Cavendish, 1993)
Examines the experiences of women in South African society, discussing their participation in various fields and profiling the lives of significant women.
Includes bibliographical references and index.
Keywords: Women -- South Africa -- Social conditions -- Juvenile literature